Public Perception of Environmental Issues in a Developing Setting: Environmental Concern in Coastal Ghana - White, Michael J. (2009)
OBJECTIVE: Balancing environmental quality with economic growth in less developed settings is clearly a challenge. Still surprisingly little empirical evidence has been brought to bear on the relative priority given environmental and socioeconomic issues among the residents themselves of such settings. This research explores such perceptions. METHODS: We undertake survey research with 2500 residents of coastal Ghana on policy issues, focusing on environmental topics. RESULTS: Our analyses reveal a significant amount of environmental awareness, with education and political engagement consistently predicting higher levels of concern. In addition, environmental issues are deemed important even when considered relative to other socioeconomic issues. CONCLUSION: In the end, we argue that our work sheds light on global environmentalism and the ways in which local populations in less developed settings prioritize social and environmental concerns. This work also has important policy implications since insight on local perceptions may help buttress policy responses designed to cope with global change.